The Esophageal-Atresia-Quality-of-life Questionnaires: Feasibility, Validity and Reliability in Sweden and Germany. Issue 4 (October 2018) - Dellenmark-Blom, Michaela; Dingemann, Jens; Witt, Stefanie; Quitmann, Julia H.; Jönsson, Linus; Gatzinsky, Vladimir; Chaplin, John E.; Bullinger, Monika; Flieder, Sofie; Ure, Benno M.; Dingemann, Carmen; Abrahamsson, Kate
ABSTRACT: Objectives: Esophageal atresia (EA) is a rare malformation characterized of discontinuity of the esophagus, concurrent with or without a tracheoesophageal fistula (TEF). We report the feasibility validity and reliability of a condition-specific quality-of-life (QOL) tool for EA/TEF children, the age-adapted EA-QOL-questionnaires, when used in Sweden and Germany. Methods: A total of 124 families of children with EA/TEF participated in the study; 53 parents completed the EA-QOL-questionnaire for children aged 2 to 7 years; 62 children/71 parents the EA-QOL-questionnaire for children 8 to 17 years. Feasibility was determined from the percentage of missing item responses. Based on clinical data and previously validated generic QOL-instruments (PedsQL 4.0, DISABKIDS-12), the final EA-QOL scores were evaluated against hypotheses of validity (known-groups/concurrent/convergent) and reliability (internal consistency/retest reliability of scores for 3 weeks). Significant level was P < 0.05. Results: In the questionnaire for EA/TEF children aged 2 to 7 years, 16/18 items were completed with missing values <6% (range 0%–7.5%), and in the questionnaire for 8 to 17-year-olds, 24/24 child-reported items (range 0%–4.8%) and 21/24 parent-reported items (range 0%–7.0%). In both age-specific EA-QOL-questionnaires, desirable standards for known-groups and concurrent validity were fulfilled; digestive symptoms and feeding difficulties negatively impacted EA-QOL-Total-scores ( P < 0.001), and as hypothesized, in 2 to 7-year-olds, respiratory symptoms decreased EA-QOL-Total-scores ( P = 0.002). Correlations between the EA-QOL and generic QOL questionnaires supported convergent validity. Internal consistency reliability was satisfactory. The level of agreements of EA-QOL-scores between the field- and retest study were good to excellent. Conclusions: The overall psychometric performance of the EA-QOL-questionnaires for EA/TEF children is satisfactory and can enhance outcome evaluations in future research and clinical practice. Abstract : Supplemental Digital Content is available in the text